Manual of clinical problems in cardiology, with annotated key references - Hillis, L. David; Ormand, Jack E; Willerson, James T (Little, Brown and Company, 1980)
Overview and an orientation to the most frequently encountered clinical problems in cardiology. Guide for medical students, house officers, and physicians in cardiology, internal medicine, and family practice.
Little, Brown spiral manual
Keywords: Heart Diseases; nemoci srdce; kardiologie